Smoking Cessation Tools in the Urological Context: Considering the Genitourinary Impacts of Smoking Cessation Tools - Nilanga Aki Bandara; Xuan Randy Zhou; Abdullah Alhamam; Peter C. Black; Marie-Pier St-Laurent (Société Internationale d’Urologie Journal)
Electronic cigarette use is rising globally. Although it may represent a potential smoking cessation tool, amidst misinformation and social media promotion, there is a growing concern regarding the health risks associated with its usage. These risks include adverse effects on the genitourinary system. This commentary investigates the genitourinary effects of approved smoking cessation tools versus electronic cigarettes, urging urologists to prioritize established methods over electronic cigarettes due to their potential for multisystem toxicity and uncertain long-term health implications. Further research is warranted to evaluate comprehensively the genitourinary effects of these interventions.